(untitled) (Itinera, 2013)
When he met the Russian philosopher Lev Shestov in Paris in 1927, the Romanian-born French poet Benjamin Fondane (1898-1944) had already written an essay on him a few years earlier. Their deep affinities ensured that they became friends, and in his conversations with Shestov Fondane discovered his own identity as a thinker. Both opposed what they saw as the imperialistic domination of Reason over European “philosophy” and theology, despite the resistance of some major figures. Both acknowleged Husserl as a great philosopher, probably the most important of his time, but they accused him, too, of placing Reason above life and above faith in God as the free Creator of the world. Even if we cannot endorse all these criticisms, they are worthy of attention as pointing to a different way of appreciating Husserl and his philosophy. Husserl is indeed much more complex than his first disciples could imagine. As a matter of fact, it is only nowadays, thanks to the University of Leuven’s ongoing publication of Husserl’s manuscript papers in the Husserliana series, that the full richness of his thought is coming into view. Fondane’s approach to Husserl is that of poet, who is also a thinker. Whereas philosophers intend to move in the realm the universal, the creative writer is able to analyse and paint the singular life, the destiny, of the characters he chooses tell stories about, and so is closer to the individual, the singular person. Fondane can thus be seen as calling Husserl to elude the domination of universal Reason by espousing more closely the texture of individual life.